2016
DOI: 10.1245/s10434-016-5461-3
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity After Inguinal Lymph Node Dissections: It Is Time for a Change

Abstract: BackgroundInguinal lymph node dissection (ILND) for stage 3 melanoma is accompanied by high wound complication rates. During the past decades, several changes in perioperative care have been instituted to decrease the incidence of these complications. This study aimed to evaluate the effect of these different care protocols on wound complications after ILND.MethodsA retrospective analysis of prospectively collected data was performed with 240 patients who underwent an ILND in the University Medical Center Gron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…While a long-term survival comparison is still pending, complete dissection provides better regional disease control and could be advocated for patients with a greater tumor burden, and the general opinion is that patients with larger metastases should still undergo lymph node dissection if no evidence of distant metastases. Patients undergoing dissection of the groin lymph nodes are particularly prone to postoperative morbidity and previous studies have suggested conservative and minimally invasive ILND protocols [ 22 , 23 ] however, these have yet to achieve broad acceptance due to the risk of compromising oncological safety. In this study, the ILND procedure is performed according to the national guidelines in Denmark, and, therefore, does not vary between study groups.…”
Section: Discussionmentioning
confidence: 99%
“…While a long-term survival comparison is still pending, complete dissection provides better regional disease control and could be advocated for patients with a greater tumor burden, and the general opinion is that patients with larger metastases should still undergo lymph node dissection if no evidence of distant metastases. Patients undergoing dissection of the groin lymph nodes are particularly prone to postoperative morbidity and previous studies have suggested conservative and minimally invasive ILND protocols [ 22 , 23 ] however, these have yet to achieve broad acceptance due to the risk of compromising oncological safety. In this study, the ILND procedure is performed according to the national guidelines in Denmark, and, therefore, does not vary between study groups.…”
Section: Discussionmentioning
confidence: 99%
“…These may be attributed mainly to the potentially contaminated groin area, division of the blood supply to the skin flaps, interruption of collateral lymphatics and the presence of a large dead space in the femoral triangle giving chance for serous or lymphatic collection. 7,[12][13][14][15] In the previous era, the treatment of groin infected grafts was total excision of the graft with massive debridement and extra-anatomical bypass. Limb loss and mortality rates were reported as 10% -79% and 9% -58%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to operatively target the sentinel node allows PC surgeons to reliably diagnose and treat metastatic disease whilst avoiding the significant morbidity of groin dissection in certain patients 19 . Patients undergoing dynamic sentinel node sampling are able to undergo a day surgery procedure through excellent teamwork between nuclear medicine radiologists and surgeons whereas those undergoing groin dissection typically have a much longer length of stay 20 .…”
Section: Diagnosis Of Metastatic Diseasementioning
confidence: 99%
“…We now know that this could lead to a critical delay in the treatment of PC. Palpable nodes are now rapidly investigated with CT scanning and ultrasound-guided fine-needle aspiration cytology or biopsy 19 .…”
Section: Diagnosis Of Metastatic Diseasementioning
confidence: 99%